Synthesis, characterizations and multivariate data analysis of non- and nitrile-functionalized N-heterocyclic carbene complexes of silver(I) and palladium(II) / Muhammad Zulhelmi Nazri ... [et al.] - Nazri, Muhammad Zulhelmi; Mohamad Zaini, Nur Syakirah; Mohamad Zaini, Nur Syakirah; Kamaruddin, Nurul Nadhirah; Rameezal, Rabia’tul Nazirah; Musa, Nur Fashya; Basar, Norazah; Razal, Mohd Rizal (Penerbit UiTM (UiTM Press), 2024)
This study reports the synthesis and comprehensive characterization of asymmetrical N-heterocyclic carbene (NHC) benzimidazolium salts and their corresponding silver(I) and palladium(II) complexes. Two series of benzimidazolium salts were synthesized: N-benzyl-N'-(n-benzonitrile) benzimidazolium bromides (1Br - 3Br, n = 2, 3, 4) and N-benzyl-N'-(nmethylbenzene) benzimidazolium bromides (4Br - 6Br, n = 2, 3, 4). The salts were prepared via N-alkylation and subsequently reacted with Ag2O to yield silver(I) NHC complexes (Ag1 - Ag6). Transmetallation of these silver complexes with Pd(COD)Cl2 produced the corresponding palladium(II) NHC complexes (Pd1 - Pd6). All compounds were characterized using melting point determination, CHN elemental analysis, FTIR-ATR, and 1Hand 13C-NMR spectroscopy. The successful formation of benzimidazolium salts was confirmed by 1H-NMR singlet peaks at δ 9.96-10.25 ppm and 13C-NMR peaks at δ 114.3-143.55 ppm. The formation of metal-NHC complexes was evidenced by the disappearance of the acidic proton and the appearance of carbene peaks in the 13C-NMR spectra. The Principal Component Analysis (PCA) was employed to explore relationships among the compounds based on their NMR data. The PCA of 1H-NMR data revealed clear separation and clustering of benzimidazolium salts and silver(I)-NHC complexes, with the first two principal components explaining 95.56% of the total variance. Similarly, the PCA of 13C-NMR data showed distinct clustering of benzimidazolium salts, silver(I)-NHC, and palladium(II)-NHC complexes, with 82.48% of the total variance explained by the first two principal components. These results demonstrate the ability of PCA to differentiate and classify the compounds based on their structural features and functional groups. This study showcases the potential of combining spectroscopic data with chemometric techniques for gaining insights into structural relationships in inorganic synthesis chemistry, which can be valuable for understanding the properties and potential applications of these NHC complexes.